False Positive Findings of [18F]PSMA-1007 PET/CT in Patients After Radical Prostatectomy with Undetectable Serum PSA Levels - Orevi, Marina; Ben-Haim, Simona; Abourbeh, Galith; Chicheportiche, Alexandre; Mishani, Eyal; Yutkin, Vladimir; Gofrit, Ofer N. (Frontiers in Surgery, 2022)
Background: PET-CT using prostate-specific membrane antigen (PSMA)-targeting radiopharmaceuticals labeled with 68Ga or 18F has emerged as the most sensitive staging tool in prostate cancer (PC). Nonetheless, the occurrence of false positive (FP) findings presents a major concern of this approach. In this prospective study, we investigated the frequency and pattern of false-positive findings of [18F]PSMA-1007 PET/CT in patients after radical prostatectomy with undetectable serum PSA levels. Any discrete non-physiological lesion of [18F]PSMA-1007 in this population is by definition FP. Methods: Seventeen men after radical prostatectomy, whose serum PSA levels were < 0.05 ng/mL at 2 – 24 months after surgery were prospectively recruited. PET/CT was acquired at both 1 h and 2 h after injection of [18F]PSMA-1007. Findings: Three studies (18%) were interpreted as completely normal. Thirty-five foci of “non-physiological” uptake were observed in the remaining 14 (82%) patients, including a single skeletal focus in four patients, multiple skeletal foci in five patients and soft tissue uptake in eight, including in a desmoid tumor and in pelvic lymphocele. The SUVmax of all lesions was in the range of 1-7, except for the desmoid tumor which measured 12.7. All foci were visible in both the 1- and the 2 h studies, presenting a minor (< 10%), statistically insignificant increase of SUVmax during this time-interval. Interpretation: FP [18F]PSMA-1007-avid foci are found in about 80% of patients with undetectable serum PSA levels. Thus, focal uptake of [18F]PSMA-1007 outside its physiological distribution is not a categorical sign of metastasis and can arise from non-specific uptake of the ligand. The interpretation of [18F]PSMA-1007 PET/CT studies should always consider the clinical context, and lesions with SUVmax < 7 are suspicious for FP.